Dysplasia and DNA ploidy to prognosticate clinical outcome in oral potentially malignant disorders. (5th January 2021) - Sathasivam, Hans Prakash; Nayar, Deepa; Sloan, Philip; Thomson, Peter J.; Odell, Edward W.; Robinson, Max
Abstract: Background: Oral potentially malignant disorders are a clinical conundrum as there are no reliable methods to predict their behaviour. We combine conventional oral epithelial dysplasia grading with DNA ploidy analysis to examine the validity of this approach to risk assessment in a cohort of patients with known clinical outcomes. Methods: Sections from diagnostic biopsies were assessed for oral epithelial dysplasia using the WHO grading system, and DNA ploidy analysis was performed using established methods. Patients reviewed for a minimum of 5 years who did not develop oral squamous cell carcinoma were classified as "non‐transforming" cases. Patients that developed oral squamous cell carcinoma ≥ 6 months after the initial diagnostic biopsy were classified as having "malignant transformation." Results: Ninety cases were included in the study. Seventy cases yielded informative DNA ploidy results. Of these 70 cases, 31 progressed to cancer. Oral epithelial dysplasia grading and DNA ploidy status were both significantly associated with clinical outcome ( P  < 0.05). Severe dysplasia had a hazard ratio of 3.50 (CI: 1.46, 8.45; P  = 0.005) compared to cases with mild dysplasia. Aneuploidy had a hazard ratio of 2.09 (CI: 1.01, 4.32; P  = 0.046) compared to cases with a diploid/tetraploid status. Receiver operating characteristic analysis gave an area under the curve of 0.617 for DNA ploidy status and 0.688 when DNA ploidy status was combined with dysplasia grading. Conclusion: Our findings suggest that combining dysplasia grading with DNA ploidy status has clinical utility which could be used to develop novel management algorithms.